The Influence of Online Shopping Experience, Customer Satisfaction and Adjusted Satisfaction on Online Repurchase Intention to Tokopedia Consumers in Surabaya - Lena Ellitan; Anthonius Richard (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Tokopedia is one of the applications that is in great demand by consumers. This study aims to examine the effect of online shopping experience, customer satisfaction and adjusted satisfaction on online repurchase intention of Tokopedia consumers in Surabaya. Based on the results of the analysis that has been carried out, it can be concluded that: Online shopping experience has a significant positive effect on customer satisfaction for consumers who shop at Tokopedia. Online shopping experience has a significant positive effect on adjusted expectations of consumers who shop at Tokopedia. Customer satisfaction has a significant positive effect on online repurchase intention on consumers who shop at Tokopedia. Adjusted expectations have a significant positive effect on online repurchase intention on consumers who shop at Tokopedia. Tokopedia, the stronger the consumer's desire to shop at Tokopedia will be.This means that the higher the consumer's expectations for Tokopedia, the stronger the consumer's desire to shop at Tokopedia will be.